2013
DOI: 10.4103/2249-4863.123919
|View full text |Cite
|
Sign up to set email alerts
|

Global cardiovascular risk assessment by family physicians in Suez canal university-family medicine centers-Egypt

Abstract: Background:The close sustained contact of family physician with their patients and local community makes preventive care an integral part of their routine work. Most cardiovascular diseases (CVD) can be prevented by addressing their risk factors. There are several guidelines that recommend different CV risk assessment tools to support CV prevention strategies.Aim:This study aimed to assess awareness and attitude of global CV risk assessment and use of their tools by family physicians; aiming to improve CV prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Our study demonstrated that documentation of 10-year global CVD risk score was poor (1.3%) despite the presence of documented individual CVD risk factors, yet this was consistent with findings from other African studies whereby in > 80% of the cases physicians documented individual CVD risk factors but did not compute global CVD risk subsequently. Although our study did not assess any determinants of the poor usage of cardiovascular risk assessment tools nor documentation of global CVD risk score, these are likely to be similar to findings from other studies from Egypt and Nigeria which reported several barriers to the use of CVD risk assessment tools by physicians such as time constraints in the clinic, cost of investigations, poor familiarity with the use of the tools and patient fears of knowing their risk status [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our study demonstrated that documentation of 10-year global CVD risk score was poor (1.3%) despite the presence of documented individual CVD risk factors, yet this was consistent with findings from other African studies whereby in > 80% of the cases physicians documented individual CVD risk factors but did not compute global CVD risk subsequently. Although our study did not assess any determinants of the poor usage of cardiovascular risk assessment tools nor documentation of global CVD risk score, these are likely to be similar to findings from other studies from Egypt and Nigeria which reported several barriers to the use of CVD risk assessment tools by physicians such as time constraints in the clinic, cost of investigations, poor familiarity with the use of the tools and patient fears of knowing their risk status [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 77%
“…The mean age of the individuals studied was congruent with the Kenya population data which showed that the majority of hypertensive individuals in Kenya are aged between 45 and 69 years [ 9 ]. Studies among physicians from different parts of Africa indicate that despite high levels of awareness of global CVD risk assessment tools and the benefits of CVD risk assessment, only a minority of physician practitioners between 23% and 28% use the tools [ 10 , 11 ]. Similar to our study, Egyptian physicians’ reliance on alternative guideline-recommended global CVD risk assessment tools was higher than the use of their national guideline-recommended tool [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a new study showed that adherence to regular follow-up in this program was low, reflecting the need to improve the program drastically [ 44 ]. Studies showed that early-career physicians with less than five years of experience are less likely to use CVD risk stratification calculators compared to more experienced physicians [ 45 ]. Thus, education of primary healthcare providers, especially younger ones, is crucial to the success of this health plan.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases can be prevented through a primary care physicians. Evidence shows such interventions are excellent economic investments because if provided early to patients, they can reduce the need for more expensive treatment [24] .…”
Section: Literature Reviewmentioning
confidence: 99%